Common reasons why an academic paper is rejected: views from the editors - Molassiotis, Alex; McCarthy, Alexandra; Charalambous, Andreas; Gibson, Faith; Lopez, Violeta; Beaver, Kinta (My University, 2019)
The editors of this journal meet many researchers at conferences and workshops who have tried and failed to publish the results of their studies. Having experienced these ourselves as authors, we do understand the frustration that potential authors often express. For those new to the publishing world, the disappointment of rejection runs deep, and often, despite very helpful reviews, that paper might never be resurrected again. The reality is that when a paper is rejected the reviewers or editors have detected significant problems with that paper that preclude its potential usefulness to our audience. In this editorial, we provide an overview of the primary reasons for rejection from the European Journal of Oncology Nursing (EJON), in the hope that authors will understand our reasoning and to help them avoid rejection in the future.
Keywords: Peer Review; Periodicals as Topic; Peer reviewers